1993
DOI: 10.2307/1940793
|View full text |Cite
|
Sign up to set email alerts
|

Autotrophic Carbon Sources for Fish of the Central Amazon

Abstract: Effective management of the Amazon's commercial fish populations requires an understanding of the factors controlling their production. A fundamental step in the investigation of fish production is to identify the plant groups that contribute energy to fish foodwebs.Stable isotope data for plants and 35 fish species were used to identify autotrophic carbon sources for the central Amazon fish community. Adult fish, aquatic macrophytes, tree parts, periphyton, and phytoplankton were collected in lakes and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
250
7
37

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(319 citation statements)
references
References 18 publications
19
250
7
37
Order By: Relevance
“…Moreover, isotopic ratios of C 3 terrestrial plants usually are assessed from very limited samples of leaves or composite sample of tree parts without consideration of variation within and among species or tissue types within a single plant (e.g., Araujo-Lima et al 1986, Forsberg et al 1993. Very little is known on isotopic variation between vegetative and reproductive tissues, despite the importance of fruit as food for large suites of invertebrates and vertebrates in both temperate and tropical ecosystems (Jordano 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, isotopic ratios of C 3 terrestrial plants usually are assessed from very limited samples of leaves or composite sample of tree parts without consideration of variation within and among species or tissue types within a single plant (e.g., Araujo-Lima et al 1986, Forsberg et al 1993. Very little is known on isotopic variation between vegetative and reproductive tissues, despite the importance of fruit as food for large suites of invertebrates and vertebrates in both temperate and tropical ecosystems (Jordano 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, Forsberg et al (1993) afirmaram que as pesquisas devem ser realizadas com combinações diferentes de enzimas puras, isto é, não somente aquelas com ações sinérgicas.…”
Section: Resultsunclassified
“…An extreme drought could result in a severe deterioration of the water quality, with high temperature and low dissolved oxygen, which would in turn have negative consequences for the quality of their food sources. For instance, it has been suggested that in addition to feeding on abundant C4 autotrophic sources (Martinelli et al, 1994), Amazonian fish would prefer to exploit C3 sources such as phytoplankton, that are easier to absorb (Forsberg et al, 1993;Mortillaro et al, 2015), but these sources have a tendency to become very scarce during extreme droughts. Both the timing and duration of extreme climatic events are therefore likely to have profound effects on life history strategies of floodplain fish (Ficke et al, 2007).…”
Section: Discussionmentioning
confidence: 99%